The current state and prospects of the nuclear power industry of China - F. F. Sharipov (Вестник университета, 2021)
China’s nuclear energy ambitions, backed by the strong financial potential of the national economy, and the consequent desire to extend its successes in international economic cooperation to the nuclear industry have attracted the researchers’ attention to a closer examination of the current state and nuclear industry prospects of China, taking into account its technological component. The unfulfilled development plan for nuclear power in the 13th Five-Year Plan, as a result of systemic mistakes and failures in the projects selected for implementation, leads to the conclusion that it is necessary to involve foreign leaders in this field, including “Rosatom” corporation, which has in its portfolio virtually verified modern technical solutions.